E-012 National Trends for the Utilization of Cerebral Angiography in Patients with Unruptured Aneurysms: 1999–2009. (26th July 2014) - Choudhri, O; Feroze, A; Mantha, A; Steinberg, G; Do, H
Abstract : Introduction: The utilization of cerebral angiography in the diagnosis and management of patients with unruptured cerebral aneurysms varies across the United States. Given advances in noninvasive imaging, such as CT and MR angiography, patients with unruptured aneurysms may never undergo cerebral angiography. This study explores shifting trends in the utilization of angiography for management of such lesions across the U. S. from 1999–2009. Methods: The National Inpatient Sample was used to identify patients carrying a primary ICD-9 diagnosis code of unruptured aneurym (430.0) between 1999–2009. The primary outcomes were compared across subgroups undergoing cerebral angiography in the management of their pathology versus those who did not. The data were analyzed using univariate and multivariate regression (SAS). Results: There were 127579 total admissions with a primary ICD-9 diagnosis of unruptured aneurysms between 1999–2009 per NIS weighted estimates. The total number of patients who underwent cerebral angiography and subsequent clipping were 19412 between 1999–2009. During the same time period 28095 patients underwent coiling after cerebral angiography. For the year 1999, 77% patients were clipped and 23% coiled after cerebral angiography (p < 0.0001). Conversely for the year 2009, 29% patients were clipped and 71% coiled after cerebral angiography (p < 0.0001). These trends were less pronounced though significant in the patients who did not undergo initial cerebral angiography, such that for the year 1999, 88% patients with unruptured aneurysms were clipped while only 12% were coiled. Conclusions: Patients with unruptured cerebral aneuryms who undergo cerebral angiography are more likely to undergo endovascular coiling rather than clipping. Disclosures: O. Choudhri: None. A. Feroze: None. A. Mantha: None. G. Steinberg: None. H. Do: None.